Desenvolvimento regional no Rio Grande do Sul : uma análise a partir de uma tipologia de políticas públicas de desenvolvimento regional - Lima, Mário Jaime Gomes de (2011)
This dissertation presents an analysis of regional development of the State of Rio Grande do Sul from the application of a typology of Regional Development Public Policy. The overall objective of the study is to analyze the construction of Public Policies on Regional Development in the State of Rio Grande do Sul, generated under the Regional Development Councils (COREDES's) give conditions for regional development as proposed by the State Constitution, along with arguments of institutionalization of regions, governance, accountability and clarity of the budget constraint. The methodological approach of the study used the application of a typology of Public Policy for Regional Development, proposed by Costa et al (2009), based on the construction of policies from different market failures in the regions. With the application of the typology of Public Policy for Regional Development, has built an array typological Public Policy for Regional Development, which made it possible to demonstrate that some COREDES's become conducive to regional development according to the typology proposed by Costa et al (2009), allowing Administrative Regionalisation as proposed by the State Constitution, unlike what happens COREDE s other's, which according to the typology applied, do not provide the necessary conditions for regional development by not completing the types of Public Policy of Regional Development of typological matrix.